Pengaruh Model Snowball Throwing Terhadap Motivasi Belajar Siswa Kelas IV DI SD Terpadu Taman Pendidikan Islam - Safina Almira Sagala; Chairunnisa Amelia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine whether there is an influence of using the Snowball Throwing learning model on the learning motivation of class IV students at the Islamic Education Park Integrated Elementary School, Medan Amplas District. This research is motivated by low motivation to learn. This is influenced by several factors, including the lack of appropriate use of supportive learning models used to increase students' learning motivation. This research is quantitative research with the type of research used, namely quasi experimental design. The variable in this research is the Snowball Throwing learning model with student learning motivation. The population and sample in this study were all students in class IV of the Islamic Education Park Integrated Elementary School, totaling 26 students. Sampling was carried out using the Cluster Random Sampling technique. Data collection techniques use tests, observation, interviews and documentation. From the results of data processing obtained from research on the application of the Snowball Throwing Model to Student Learning Motivation in class IV of the Islamic Education Park Integrated Elementary School, Kec. Medan Amplas, Medan City, Observed learning motivation was influenced by using the snowball throwing learning model on student learning motivation.